Delaying Candidatus Liberibacter asiaticus infection of citrus trees through use of individual protective covers and systemic delivery of oxytetracycline - Tardivo, Caroline; Monus, Brittney; Pugina, Gabriel; Strauss, Sarah L.; Alferez, Fernando; Albrecht, Ute (Frontiers in Plant Science, 2025)
Huanglongbing (HLB), or citrus greening, remains one of the most destructive diseases affecting citrus production globally. Associated with the phloem-limited bacterium Candidatus Liberibacter asiaticus (CLas) and vectored by Diaphorina citri, HLB leads to canopy decline, fibrous root loss, and reductions in fruit yield and quality. Recently, the systemic delivery of oxytetracycline (OTC) via trunk injection was approved in Florida as a targeted therapy to reduce CLas titers and improve tree health. In parallel, Individual Protective Covers (IPCs) have been adopted to delay CLas infection in newly planted citrus trees by vector exclusion. This study investigates the combined use of IPCs and trunk injection of OTC for post-IPC therapy. ‘Valencia’ sweet orange trees grafted on US-812 and US-942 rootstocks were planted in December 2020 under HLB-endemic conditions in southwest Florida. IPCs were installed at planting and removed after 18 months. The first OTC injection was performed in May 2023, 10 months after IPC removal. A second injection was performed in May 2024. A 2 × 2 × 2 factorial experimental design evaluated the effects of infection history (early-infected and late-infected), rootstock cultivar (US-812 and US-942), and injection treatment (OTC-injected and non-injected) on tree responses over two consecutive production seasons. In year 1, infection history significantly influenced tree size, fruit yield, total soluble solids (TSS), TSS/titratable acidity ratio, and peel color. Late-infected trees outperformed early-infected trees, regardless of injection treatment and rootstock cultivar. In year 2, OTC-injected trees exhibited significantly higher yields, improved juice quality, and enhanced canopy health regardless of infection history and rootstock cultivar. Fibrous root microbiome analyses based on 16S rRNA sequencing revealed no significant effects of OTC injection on bacterial alpha or beta diversity, with stable community structure observed across treatments and time points. This suggests that targeted vascular delivery of OTC may not cause any major disruption to the root endorhizosphere microbiome. Together, the results from this study demonstrate the efficacy of integrating preventative (use of IPCs) and therapeutic (OTC vascular delivery) strategies for sustainable HLB management while preserving microbial integrity and offering a model for citrus production in parts of the world where HLB is prevalent.